2017
DOI: 10.1103/physrevb.96.045407
|View full text |Cite
|
Sign up to set email alerts
|

Resonantly excited exciton dynamics in two-dimensional MoSe2 monolayers

Abstract: We report on the exciton and trion density dynamics in a single layer of MoSe2, resonantly excited and probed using three-pulse four-wave mixing (FWM), at temperatures from 300 K to 77 K . A multi-exponential third-order response function for amplitude and phase of the heterodyne-detected FWM signal including four decay processes is used to model the data. We provide a consistent interpretation within the intrinsic band structure, not requiring the inclusion of extrinsic effects. We find an exciton radiative l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 49 publications
4
37
0
Order By: Relevance
“…We now analyze the origin of the oscillations in the 2D maps with the goal to deduce the EXPC strength. Previous experiments reported that the trion signal in 1L-MoSe2, located ~0.03 eV below the neutral exciton peak 54 , gradually dies out both in PL and absorption when T increases from 15 to 295 K 25,54 . The electronic coupling between excitons and trions, observed at 20 K in Ref.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We now analyze the origin of the oscillations in the 2D maps with the goal to deduce the EXPC strength. Previous experiments reported that the trion signal in 1L-MoSe2, located ~0.03 eV below the neutral exciton peak 54 , gradually dies out both in PL and absorption when T increases from 15 to 295 K 25,54 . The electronic coupling between excitons and trions, observed at 20 K in Ref.…”
Section: Resultsmentioning
confidence: 96%
“…Optical four-wave-mixing experiments in semiconductors provide access to coherent dynamics of excitons [23][24][25]10 . In photon echo experiments the polarization state of incident photons (circular or linear) allows one to uncover different mechanisms behind the signal formation 26,27 .…”
mentioning
confidence: 99%
“…The different relaxation processes contribute to the FWM amplitude with different phases, imprinting unusual signatures in the measured density dynamics of the FWM amplitude due to constructive and destructive interferences. 38…”
Section: Resultsmentioning
confidence: 99%
“…After the resonant excitation, several relaxation mechanisms play an important role. 38 They are governed by, on the one hand, the high oscillator strength 43 and thus fast radiative recombination rate and, on the other hand, by the EX conversion toward different dark states, resulting from the peculiar valley structure and available scattering channels with phonons, charge carriers, and EXs. Due to this scattering and radiative recombination, the EX phase is lost on a picosecond time scale, as shown by the results discussed in the previous sections.…”
Section: Resultsmentioning
confidence: 99%
“…For a quantitative analysis, the population decay data is fitted with the complex multi-exponential response function, as explained in detail in ref. 35 :…”
Section: Heterodyne-detected Four-wave Mixing: Complex Fit To the Excmentioning
confidence: 99%